Lecturers’ Perspectives on using KeLiP as an E-Learning Tool - Hassan, Hasni; Mohd Tahir, Izah; Wan Isa, Wan Malini (2011)
The aim of this paper is to investigate the use of an e-learning tool called KeLiP among lecturers in one of the public university in Malaysia, University Sultan Zainal Abidin (UniSZA). Specifically, this study is intended to achieve three main objectives: to examine the opinions of lecturers towards KeLiP, to investigate willingness to use KeLiP and to examine the challenges using KeLip. A total of 250 lecturers responded to the survey. Interestingly, the experiences on internet and computers as well as exposure on the use of KeLiP among lecturers were vast. The results on opinions revealed that KeLiP is cost effective and easy to understand. The results also indicate that the main challenge faced in using KeLip was related to technical problems and lecturers were willing to use KeLiP if appropriate support is given.